2018
DOI: 10.3324/haematol.2018.205880
|View full text |Cite
|
Sign up to set email alerts
|

DUSP22-rearranged anaplastic lymphomas are characterized by specific morphological features and a lack of cytotoxic and JAK/STAT surrogate markers

Abstract: DUSP22-rearranged anaplastic lymphomas are characterized by specific morphological features and a lack of cytotoxic and JAK/STAT surrogate markers ALK-negative anaplastic large cell lymphoma (ALKnegative ALCL) is a heterogeneous disease with very disparate outcomes. Molecular studies have identified chromosomal rearrangements involving the DUSP22-IRF4 locus on 6p25.3 (DUSP22 rearrangements) as a favorable prognostic factor, associated with complete remission after first treatment thereby suggesting that this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 10 publications
2
48
0
Order By: Relevance
“…The possible reason to our data might be that: JKAP might directly regulate the signal transducer and transcription activator signal transducer and activator of transcription 3 (STAT3), which attenuated its activity through dephosphorylation of STAT3 at Tyr705 and Ser727, and subsequently regulated the differentiation of Th17 cells, thereby reduced the CD risk, activity, and inflammation. [20,21] JKAP might also inhibit T-cell-mediated immune activity through other pathways such as mitogen-activated protein kinase / extracellular signal-regulated kinase pathway and stress-activated protein kinase/JNK pathway, or through inactivating Lck (a src-family tyrosine kinase) by dephosphorylating Tyr394 during T-cell receptor signaling, thus the declined JKAP expression was correlated with increased disease risk, activity, and inflammation. [9,13,22]…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason to our data might be that: JKAP might directly regulate the signal transducer and transcription activator signal transducer and activator of transcription 3 (STAT3), which attenuated its activity through dephosphorylation of STAT3 at Tyr705 and Ser727, and subsequently regulated the differentiation of Th17 cells, thereby reduced the CD risk, activity, and inflammation. [20,21] JKAP might also inhibit T-cell-mediated immune activity through other pathways such as mitogen-activated protein kinase / extracellular signal-regulated kinase pathway and stress-activated protein kinase/JNK pathway, or through inactivating Lck (a src-family tyrosine kinase) by dephosphorylating Tyr394 during T-cell receptor signaling, thus the declined JKAP expression was correlated with increased disease risk, activity, and inflammation. [9,13,22]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a peripheral T cell lymphoma not otherwise specified (NOS) should be taken into account; however, according to the World Health Organization (WHO) recommendations both the morphology and phenotype of the current biopsy support the diagnosis of an ALK-negative, anaplastic large cell lymphoma [15]. The diagnosis is further supported by detection of the IRF4/DUSP22 translocation [16] and was confirmed independently by the institute of neuropathology Cologne, Germany.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Approximately half of the patients diagnosed with ALCL have ALK-positive status and have high response to standard chemotherapy regimen consisting of cyclophosphamide, doxorubicin, vincristine, and prednisone or prednisolone (CHOP) (6). Contrastingly, due to inefficacy of standard regimens, patients with ALK-negative ALCL often undergo more intensive therapies than ALK-positive ALCL patients (7)(8)(9). A growing number of studies have reported that the 5-year survival of a subset of ALK-negative ALCL patients with dual specificity phosphatase 22 (DUSP22) rearrangement was comparable to that of ALK-positive ALCL patients who received the same treatment regimen (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, due to inefficacy of standard regimens, patients with ALK-negative ALCL often undergo more intensive therapies than ALK-positive ALCL patients (7)(8)(9). A growing number of studies have reported that the 5-year survival of a subset of ALK-negative ALCL patients with dual specificity phosphatase 22 (DUSP22) rearrangement was comparable to that of ALK-positive ALCL patients who received the same treatment regimen (9)(10)(11). Routine stem cell transplantation may lead to overtreatment for subsets of ALK-negative ALCL patients, such as those with DUSP22 rearrangement, resulting in unnecessary increases in costs and risks for those patients.…”
Section: Introductionmentioning
confidence: 99%